2011
DOI: 10.4103/0971-3026.85372
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging in spinal cord injury

Abstract: Background and Purpose:To assess the feasibility of spinal tractography in patients of spinal cord injury vs a control group and to compare fractional anisotropy (FA) values between the groups.Materials and Methods:Diffusion tensor imaging (DTI) was performed in the spinal cord of 29 patients (18 patients and 11 controls). DTI was done in the cervical region if the cord injury was at the dorsal or lumbar region and in the conus region if cord injury was in the cervical or dorsal region. FA was calculated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
5
16
0
Order By: Relevance
“…By comparing FA values of the whole cord section, at 12, 3, 6 and 9 o'clock below the most affected disc with FA values opposite to normal cord level (C2-C2/3), we found highly significant FA value reduction with P value = 0.001. This matches with Kamble et al [13] who found that FA values are decreased below the site of injury, likely due to Wallerian degeneration.…”
Section: Discussionsupporting
confidence: 91%
“…By comparing FA values of the whole cord section, at 12, 3, 6 and 9 o'clock below the most affected disc with FA values opposite to normal cord level (C2-C2/3), we found highly significant FA value reduction with P value = 0.001. This matches with Kamble et al [13] who found that FA values are decreased below the site of injury, likely due to Wallerian degeneration.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies [34][35][36] about CSM offer a comparative analysis between the CSC DTI parameters according to age and lesion site, but without considering the combined influence of age and segments. The same is true for MRI studies of spinal cord trauma [37,38]. In the future, we should fully consider these factors to avoid the interference of confounding factors.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies of the spinal cord indicate the large disagreement in the applied number of directions. [25][26][27][28] When establishing a DTI protocol for clinical implementation, it is critical to consider the number of gradient directions of the DTI scheme in terms of the overall goal of the study. Consistent with other studies, we observed that a scan time equivalent gradient scheme of 6 directions is significantly worse than a gradient scheme of 15 or 32 directions in estimation for DFA, 15 but we further reveal that these trends are also observed for DAD and DRD.…”
Section: Discussionmentioning
confidence: 99%